Determination Whether There is Any Correlation Between the Levels of Strategic Planning on Marketing, Technological and Financial Performance of Bank of Baroda Kenya East Africa - Gichung’wa, Miriam Wanjiku; Nyakweba, Thomas Ombui; Muchai, Peter Muthama (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
This study was undertaken with the primary purpose of determining whether there was any correlation between the level of strategic planning on marketing performance’ technological performance and financial performance of bank of Baroda. To accomplish this task, data was collected from a sample of small number to present each of the bank’s department and customers along with information from other Banks data base. The focus was on correlation between strategic planning and marketing performance, financial performance and technological performance. The research was carried out using a questionnaires, opinions and observations, based upon a purposive and simple sample of the bank in the target population. The data was analyzed using the package of social science of statistics and analysis of Karl Pearson’s coefficient of correlation as appropriate. The findings of this study revealed that there was correlation between the level of planning activities carried out by a financial institution and the performance of the bank as measured by the Return on Assets, the Return on Equity, and the Net Interest Margin, customer satisfaction, quality of services, product quality, brand, brand name, time frame, costs, efficiency and effectiveness. The findings also revealed that there was correlation between the level of planning carried out by the financial institution and the management characteristics measured. The findings also found correlation between the level of planning carried out and the size of the bank’s departments within the target population. These results were consistent and reaffirmed several prior studies indicating that there was correlation between the level of impacts of strategic planning and performance of the bank output. The findings also found correlation between the level of planning carried out and the size of the bank’s departments within the target population. On overall the researcher found out that there was a correlation between strategic planning and Marketing, Financial, Technological performance.